2006
DOI: 10.1590/s0074-02762006000300011
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and cytotoxic activity of Brazilian plant extracts - Clusiaceae

Abstract: Twelve extracts obtained from nine plants belonging to six different genera of Clusiaceae were analyzed against Gram-negative (Escherichia coli and Pseudomonas aeruginosa) and Gram-positive (Staphylococcus aureus and Enterococcus faecalis) bacteria using the microdilution broth assay. Tovomita aff. longifolia, T. brasiliensis, Clusia columnaris, Garcinia madruno, Haploclathra paniculata, and Caraipa grandifolia extracts showed significant results against the bacteria. The organic extract obtained from the leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 20 publications
5
29
1
2
Order By: Relevance
“…This composition makes the cell wall impermeable to lipophilic solutes, and the porins in the cell wall do not allow the penetration of high molecular mass hydrophilic solutes, with an exclusion limit of about 600 Da. This data is also supported by previous workers (Nair and Chanda, 2006;Suffredini et al, 2006;Kang et al, 2006). Furthermore, it has been proposed that the mechanism of the antimicrobial effects involves the inhibition of various cellular processes, followed by an increase in plasma membrane permeability and finally ion leakage from the cells (Walsh et al, 2003).…”
Section: Resultssupporting
confidence: 87%
“…This composition makes the cell wall impermeable to lipophilic solutes, and the porins in the cell wall do not allow the penetration of high molecular mass hydrophilic solutes, with an exclusion limit of about 600 Da. This data is also supported by previous workers (Nair and Chanda, 2006;Suffredini et al, 2006;Kang et al, 2006). Furthermore, it has been proposed that the mechanism of the antimicrobial effects involves the inhibition of various cellular processes, followed by an increase in plasma membrane permeability and finally ion leakage from the cells (Walsh et al, 2003).…”
Section: Resultssupporting
confidence: 87%
“…There are negative as well as positive reports on the antibacterial activity of methanol extracts from C. macrostachyus leaves (Matu and Van Staden, 2003;Wagate et al, 2010;Jackie et al, 2016). Contrasting results could be attributed to the locality of plant species, parts used, time of collection, storage conditions, and methods of analysis (Suffredini et al, 2006;Jackie et al, 2016). Even though the majority of the Ethiopian population uses C. macrostachyus to treat different diseases traditionally, a single study was conducted regarding the antibacterial effect of C. macrostachyus leaf but there is no study conducted on the other parts of this plant in Ethiopia.…”
Section: Introductionmentioning
confidence: 98%
“…Some of these Clusia species present antibacterial activity (Lokvam and Braddock, 1999;Porto et al, 2000). Suffredini et al (2006) observed that Clusia columnaris and other Clusiaceae have antibacterial and cytotoxic activity. A survey by Porto et al (2000) on the bioactivity of all methylated and non-methylated resins and bee nest extract using bioautography (Betina, 1973) revealed that non-methylated polyisoprenylated benzophenones are largely responsible for the antimicrobial activity of pure floral resins and of the nest extract.…”
Section: Resultsmentioning
confidence: 99%